P-100 CORRELATION OF TWO TRANSIENT ELASTOGRAPHY EQUIPMENT FOR ESTIMATION OF LIVER STEATOSIS AND LIVER FIBROSIS - Raul Alfonso Gomez Mendoza; Eva Juarez Hernandez; Montserrat Berrospe Alfaro; Regina Lopez De Cardenas Rojo; Martha Helena Ramos Ostos; Graciela Castro Narro; Ivan Lopez Mendez (Annals of Hepatology)
Conflict of interest: No Introduction and Objectives: Transient elastography (TE) is an alternative diagnostic tool for estimating liver steatosis and fibrosis. Two ET devices, iLivTouch®/UAP and Fibroscan®/CAP, have shown similar diagnostic accuracy; however, no studies have evaluated the correlation of liver steatosis and fibrosis measurements between both devices in the Mexican population. Aim: To evaluate the correlation of measurement values of liver steatosis and liver fibrosis using iLivTouch®/UAP and Fibroscan®/CAP. Patients / Materials and Methods: This prospective study included adult patients who attended a check-up unit. The evaluation of liver steatosis and liver fibrosis was performed using TE with two devices (iLivTouch® FT100 and Fibroscan® 502 Touch), meeting the reliability parameters. The correlation of measurements was evaluated with the Pearson correlation coefficient; meanwhile, a Student's t-test was performed to determine differences in dB/m and kPa means. Results and Discussion: A total of 69 patients were included; 57% (n=40) were men, with a mean age and body mass index of 45±10 years and 22.4±4.5 kg/m2, respectively. The prevalence of diabetes mellitus was 7.2% (n=5). The mean dB/m and kPa were 266±42 dB/m and 5.8±1.2 kPa with iLivTouch® and 243±56 dB/m and 4.0±0.8 kPa with Fibroscan®. The prevalence of liver steatosis was 29% (n=20) by iLivTouch® and 20% (n=14) by Fibroscan® (p=0.32), while fibrosis was 49.3% (n=34) and 2.9%. (n=2), respectively, (p=0.0001). The mean difference for dB/m was -22.6, p≤0.0001, while for kPa, the difference was 1.72, p≤0.0001. According to the correlation analysis, this was r=0.73 (strong), p≤0.0001 for the estimation of liver steatosis, and r=0.35 (moderate), p=0.003 for the estimation of liver fibrosis. Conclusions: TE devices iLivTouch® and Fibroscan® show a strong correlation for estimating liver steatosis and a moderate correlation for estimating liver fibrosis.